Mulheres infanticidas: o crime de infanticídio na Cidade de Fortaleza na primeira metade do Século XX - Atayde, Marla Albuquerque (2007)
The main point of this research is to analyze the practice of the crime of Infanticide in the city of Fortaleza in the first half of Century XX. We have as starting point, the process-crime, which they are historical object, the "women infanticides" that will provide quite information to the analyze of this project. In the process-crime of Infanticide, we will find women who had killed their own children, at the birth moment. Beyond the criminal proceedings, we have the notice of Infanticide published at local newspaper. With these elements, we face with some questions, such as: Infanticide category, while crime, is a social definition, being able to have various definitions depending on the regulation spaces of the environment. Like Brazilian Legislation in its criminal statutes considered the fact of the woman to kill her proper son. As they are composed, in its narratives and infanticides were explained by the "women infanticides" the reasons for the commitment of the crime, analyzing as they were judged, observing questions, as the defense of the proper honor, the puerperal state and social-economic factor. As they had been analyzed, by the Medical Knowledge the cases of Infanticide. As the crimes of Infanticide and the women who had committed them they were written in the Newspaper of the city. The investments had been given, especially from Periodicals, in relation to the naturalization of the maternal love and the valuation of the child. As "women infanticides" had been given to the relations among the neighbors, family and witnesses. As it seemed to be essential, the occultation of the pregnancy and the just-been born one. Finally, analyzing the processes of choices that triggered in crimes of these women, we perceive as, many times, honor if it confused with survival.